(3GdCUhd GdKeGfjI aj GdEjeGfs - (3eMeO Hf GdbGSe Hf EHQGgje Hf ESeGYjd, Hf Ydj Hf CHj WGdHs
(3ChdgG (B:s
(3HSe Gddg GdQMef GdQMje hHg fSJYjf GdMeO ddg GdeJaVd GdcQje GdefYe Ydi YHGOg NCdag HHQGgjf GdYbhd hGdJfRjd hGdehUhd hELeGY GdYdeGA s
(3BNQgG (B:s
(3hGdMeO ddg Gdehab ddHjGf hGdgGOi dcd EfSGf Je GdcJGH Yf Gddg GdYRjR GdefGf s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
Keywords: (3GdJhMjO hGdedd hGdfMds